Peran Kepemimpinan dalam Membangun Budaya Kerukunan Antara Organisasi dan Masyarakat: Studi kasus K3TA (Kerukunan Keluarga Kalimantan Tulungagung) - Sirojuddin, Ahmad Sholihin; Bramayudha, Airlangga; Novitasari, Nur Laila (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi UIN Sunan Ampel Surabaya, UIN Sunan Ampel Surabaya, 2025)
This research combines case study and literature study approaches to analyse the leadership dynamics and practice of harmony in the K3TA congregation in Kampungdalem Tulungagung. To strengthen the validity of the findings, researchers conducted case studies and source literature studies by comparing field data and literature related to leadership, harmony, and culture. The literature study focused on references on leadership and strategies to preserve traditions in a multicultural society. The results showed that Habib Sholeh Asegaff as chairman of K3TA combines transformational and charismatic leadership styles. This is reflected in his priority towards the sustainability of the organisation, his ability to motivate members through emotional closeness, and his skills in actualising the vision-mission into concrete actions. On the other hand, his efforts to maintain the harmony of the Banjar community are carried out by maintaining the K3TA tradition consistently since ancestral times, without much change, while building an inclusive cross-cultural dialogue.